2016
DOI: 10.1111/tbed.12516
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Mortality, Vesicular Lesions and Lameness Associated with Senecavirus A in a U.S. Sow Farm

Abstract: A 300-sow farrow-to-finish swine operation in the United States experienced a sudden and severe increase in mortality in neonatal piglets with high morbidity followed by vesicular lesions on the snout and feet of adult females and males. Affected live piglets were submitted for diagnostic investigation. Samples tested polymerase chain reaction (PCR) negative for foot-and-mouth disease virus, porcine delta coronavirus, porcine epidemic diarrhoea virus, porcine rotavirus types A, B and C, transmissible gastroent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 6 publications
2
93
0
1
Order By: Relevance
“…SVA was also found in lesions in pigs suffering from porcine idiopathic vesicular disease in Canada and USA in 2008 and 2012, respectively [11]. In 2014 and 2015, SVA infection was associated with outbreaks of vesicular disease in sows as well as neonatal pig mortality in Brazil and USA [12]. In China, SVA (SVV CH-01-2015) was also first isolated in a pig farm in 2015 [13].…”
Section: Introductionmentioning
confidence: 99%
“…SVA was also found in lesions in pigs suffering from porcine idiopathic vesicular disease in Canada and USA in 2008 and 2012, respectively [11]. In 2014 and 2015, SVA infection was associated with outbreaks of vesicular disease in sows as well as neonatal pig mortality in Brazil and USA [12]. In China, SVA (SVV CH-01-2015) was also first isolated in a pig farm in 2015 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Death was observed in neonatal piglets after sows exhibited clinical symptoms. In contrast, the report described that clinical signs in the neonatal piglets preceded vesicular signs in adult animals (Canning et al., ). On the basis of this analysis and previous work, it seems that SVA might be one of causes of PIVD.…”
Section: Discussionmentioning
confidence: 96%
“…The fourth report showed that the mortality rate of neonatal piglets ranged from 30% to 70% in SVA‐affected herds in Brazil (Vannucci et al., ). Furthermore, SVA was recently isolated from neonatal piglets and it is the first report linking SVA with severe neonatal death in America (Canning et al., ). Three reports described detection and genomic characterization of SVA in the United State in 2015 (Guo et al., ; Hause et al., ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Senecavirus A circulation in Brazil has already been characterized based on molecular epidemiology as well as associated to the occurrence of clinical signs in neonatal pigs (Laguardia‐Nascimento et al., ; Leme et al., ). On a global scale, Canada, USA, Colombia, China and Thailand are countries that have already reported this emerging virus related to swine vesicular disease (Canning et al., ; Guo et al., ; Hause, Myers, Duff, & Hesse, ; Joshi et al., ; Pasma et al., ; Qian, Fan, Qian, Chen, & Li, ; Saeng‐chuto, Rodtian, Temeeyasen, Wegner, & Nilubol, ; Sun, Vannucci, Knutson, Corzo, & Marthaler, ; Tousignant et al., ; Wang, Prarat, Hayes, & Zhang, ; Wu et al., ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%